Analysis of High School Biology Teachers’ Pedagogical Competence in Implementing Differentiated Instruction and Social-Emotional Learning in Aceh Province - Seri Amalia; Wiwit Artika; Samingan Samingan; Hafnati Rahmatan; Muhibbuddin (UNIVERSITAS PGRI MADIUN, 2026)
The Merdeka Curriculum, with its core principle of “Merdeka Belajar”, empowers teachers to design and implement innovative teaching methods, including differentiated instruction and social-emotional learning. Teachers’ instructional competencies play a significant role in the successful implementation of the curriculum. This study aims to analyze the pedagogical competencies of high school biology teachers in Aceh Province in implementing Differentiated Instruction (DI) and Social-Emotional Learning (SEL), to compare the competencies and perceptions between Transformational Teachers (TTs) and Non- Transformational Teachers (NTTs), and to examine the relationship between the two. The research sample consisted of 286 teachers, comprising NTTs (n = 223) and TTs (n = 63) from a total population of 1,603 high school biology teachers in Aceh Province. The research instrument utilized a questionnaire on the implementation of DI and SEL. The results indicate that most biology teachers in Aceh Province, both TTs and NTTs, possess pedagogical competencies in the Good to Very Good categories regarding the implementation of DI and SEL. A comparative analysis also revealed significant differences in competencies, with TTs demonstrating superior performance in applying DI and SEL than NTTs. The Spearman correlation test showed a very strong, significant positive relationship between the implementation of DIL and SEL (r = 0.837, p < 0.001). This indicates that the higher a teacher's competence in applying differentiation principles, the greater their ability to manage students’ social-emotional needs. It is hoped that this will provide recommendations for education policymakers in Aceh in designing more targeted training strategies to reduce competency gaps among teachers in the field.This study provides a mapping of Biology teachers’ competencies in Aceh regarding the implementation of DI and SEL, serving as an empirical foundation for evaluating the effectiveness of teacher professional development programs.